Methods of organization of SCORM-compliant teaching materials in electronic format - Jacek Marciniak (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
This paper presents a method of organizing electronic teaching materials based on their role in the teaching process rather than their technical structure. Our method allows SCORM materials stored as e-learning courses ("electronic books") to be subdivided and structured so that content can be used in multiple contexts. As a standard, SCORM defines rules for organizing content, but not how to divide and structure it. Our method uses UCTS nomenclature to divide content, define relationships between content entities, and aggregate those entities into courses. This allows content to be shared in different implementations of SCORM while guaranteeing that usability and consistency are maintained.